Analysis of the Effect of Compensation, Motivation, and Work Environment on Job Satisfaction and Employee Job Loyalty Using the Partial Least Square (PLS) Method at PT. XYZ - Syarif, Muhammad; Iriani, Iriani (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT.XYZ engaged in the wood processing industry by producing and exporting plywood. Based on preliminary research conducted, it is known that the current condition is that there are problems regarding decreased job satisfaction which results in a low employee work loyalty attitude towards the company. The purpose of this study is to determine the effect of compensation, motivation, and work environment on job satisfaction, to determine the effect of job satisfaction on employee job loyalty, and to provide suggestions for development and improvement to companies related to human resource management. All permanent employees of the production division PT. XYZ is the research population totaling 95 people, with a sample size of 50 employees. The research method is quantitative using a questionnaire with a scale of 1 to 5. The data analysis technique in this study uses the Structural Equation Modeling-Partial Least Square (SEM-PLS) method. The results showed that compensation has a significant effect on job satisfaction, motivation has a significant effect on employee job satisfaction, work environment has a significant effect on employee job satisfaction, and job satisfaction has a significant effect on employee job loyalty.